OP35 The Health Impacts of Free Bus Travel for Young People in London. (17th September 2012) - Edwards, P; Steinbach, R; Wilkinson, P; Petticrew, M; Goodman, A; Jones, A; Roberts, H; Kelly, C; Nellthorp, J; Green, J
Abstract : Background: Interventions in transport systems have potentially far-reaching impacts on public health, but can be challenging to evaluate. In 2005, young people in London gained access to free bus travel; an intervention that has a number of potential risks and benefits to health. As transport access is linked to well-being, we might expect the policy to benefit the health of young people by reducing transport exclusion. However, health effects might also include: young people doing less walking, thus reducing levels of physical activity, but also reducing exposure to pedestrian injury risk; or being more exposed to assault as they travel further. Methods: We utilized change-on-change analyses comparing pre (2001–2004) and post (2006–2009) changes in outcomes in 'younger people' (intervention group, 12–17 years) to 'adults' (control group, 25–59 years) in London, UK. Main outcome measures included changes in travel patterns (trips made by main travel mode and distances travelled), road traffic injuries and hospital admissions for assault. Results: Post-intervention, the total number of journeys to school or work made by younger people increased relative to adults (change-on-change ratio 1.19: 95% CI 1.13–1.25), and the proportion of short trips (<1km) by bus doubled (1.97: 1.07–3.84). There was some evidence that younger people made fewer trips where walking was the main mode of travel (0.76: 0.70–0.85), but no evidence for a change in overall distances walked by younger people post-intervention. Against background declines in road traffic injury, the decrease in road injury to young people was larger relative to adults (0.84; 0.82–0.87), however pedestrian injuries declined similarly in both groups. Rates of hospitalisation due to assaults increased in younger people relative to adults (1.20: 1.13–1.27). Conclusion: A change in the distribution of travel modes used by younger people (relative to adults who had not received free bus travel) was observed post-intervention. Younger people made fewer trips where walking was their main mode of travel, but there was little overall difference in distances walked, suggesting that the policy may have generated journeys but made little overall impact on prevalence of active transport. Observed changes in road traffic injuries reflect the relative risks of changing travel modes. The intervention has been associated with a small relative increase in assaults to younger people. A change-on-change analysis has enabled us to use this 'natural experiment' to quantify some important health outcomes of a transport policy in the absence of evidence from a randomised trial.